'Without Sultan Qaboos, We Would Be Yemen': The Renaissance Narrative and the Political Settlement in Oman. (6th July 2017) - Phillips, Sarah G.; Hunt, Jennifer S.
Abstract: Oman's developmental trajectory is a 'positive outlier' to most post‐colonial states, particularly those with significant natural resource reserves. Its trajectory confounds many of the usual expectations surrounding the impact of rentier incomes on conflict and inclusive development. This piece attempts to disentangle the threads of Oman's apparent good fortune to reveal characteristics of its political settlement that may (and may not) have salience elsewhere. This paper spotlights the influence of narrative and the non‐domestic factors that played pivotal roles in the formation and evolution of the political settlement, suggesting that both have generally been understated within the literature to date. © 2017 The Authors Journal of International Development Published by John Wiley & Sons Ltd